Development of Catamaran Fishing Vessel - Setyawan, D.; Utama, I K. A. P.; Murdijanto, Murdijanto; Sugiarso, A.; Jamaluddin, A. (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2010)
Multihull due to a couple of advantages has been the topic of extensive research work in naval architecture. In this study, a series of investigation of fishing vessel to save fuel energy was carried out at ITS. Two types of ship models, monohull (round bilge and hard chine) and catamaran, a boat with two hulls (symmetrical and asymmetrical) were developed. Four models were produced physically and numerically, tested (towing tank) and simulated numerically (CFD code). The results of the two approaches indicated that the catamaran mode might have drag (resistance) smaller than those of monohull at the same displacement. A layout of catamaran fishing vessel, proposed here, indicates the freedom of setting the deck equipments for fishing vessel.